How Religiosity Affect Climate Change? A Cross-Country Analysis - Agusalim, Lestari; Karim, Muhamad (International Journal of Energy Economics and Policy, 2024)
Climate change demands a collective response, including from religious perspectives, but it presents a dualistic challenge. On one hand, some believers see it as a divine, immutable law (theocentric), urging humans not to defy it. Conversely, others attribute climate change to human actions that exploit nature (anthropocentric). This study scrutinizes the relationship between religiosity and climate change, using per capita CO2 emissions as a proxy. It employs cross-country regression analysis, along with robustness and sensitivity tests. The findings highlight religiosity's substantial role in curbing per capita CO2 emissions growth. This underscores religion's potential as a societal force in overcoming environmental problems, global climate issues, safeguarding natural resources and ecosystems, and ensuring a comfortable, secure existence on Earth.